Design of a mechanism based on virtual reality to improve the ability of graduated motor imagery, using the brain computer interface - Auccahuasi, W. (2019)
Graduated motor imagery is the technique used in rehabilitation therapies, for the treatment of chronic pain and in most cases for movement disorders, the technique consists in strategically presenting therapies that correspond to laterality perception, mirror therapies and motor imagery. In the present work a mechanism was designed that facilitates the patient to learn about the movement mechanisms and the way in which the movement interacts with the extremities of the upper and lower limbs, the design is based on being able to use 24 images of the upper limbs and lower, these images are grouped into two groups with a different background, one dark and the other light, these images are grouped and sequentially arranged in a video, each image has a duration of 2 seconds in the video, after this time the image, at the time each image is displayed, the patient raises his hand that corresponds to the image he is observing, if he observes an upper or lower limb that corresponds to the right side, the patient will raise his right hand, in order to eliminate any visual pollution that does not achieve concentration to the patient, the use of the virtual reality lens that is coupled is used side with a cellular equipment that is where the video can be observed, the proposal provides a brain computer interface with which the level of concentration and meditation of the patient is measured at the time of performing the technique.